Chebyshev Polynomials in Collocation Methods for Solving Singular Perturbation Problems - Mindeel M. Al-Abrahemee, Khalid (Al-Qadisiyah Journal of Pure Science, 2018)
â€œThis paper discourse the utility Momentmethod on second, third and fourth kind Chebyshev polynomials as attempt functions in solution singular perturbation problems with boundary conditionâ€. â€œThe process is computational very unmingled and magneticâ€. â€œApplications are justly demonstrated through numerical examples to illustrated the effectiveness and easiness of the approximate, all the calculation outcome are obtain using Matlabâ€.